Efectos contables y tributarios en los sujetos pasivos al ser obligados por la administración tributaria a llevar contabilidad. - Paredes Cruz, Liliana Maribel (2014)
This research work was intended to have a detailed accounting and tax effects of city taxpayers Window and responsibilities that must comply with the Internal Revenue Service, the natural person must be designated to take accounting, among these effects, is the lack of information on the processes to be followed in the declarations and payment of taxes; ignorance of deductible expenses for the payment of income tax, or know why the IRS chose accounting as required to keep taxpayers. Parallel to the taxpayers, the case study of Mr. José Luis Fernández Quino was determined and the parameters used by the Internal Revenue Service (IRS) to designate it as a taxpayer to maintain accounting records are established, identifying which fully comply with tax obligations issued by SRI…………….